1987
DOI: 10.1159/000234397
|View full text |Cite
|
Sign up to set email alerts
|

Transient Elevation of Serum IgE after Allogeneic Bone-Marrow Transplantation

Abstract: Serum IgE levels were followed longitudinally twice a week for up to 100 days in 60 children treated for leukemia, severe aplastic anemia or severe combined immunodeficiency: 52 underwent allogeneic bone-marrow transplantation and 8 immunosuppressive treatment. In 55 of 58 treatment periods which could be analyzed (95%), a transient sharp increase of serum IgE was detected, irrespective of the initial diagnosis and mode of treatment. A second IgE peak was recorded in 16% of evaluable treatment periods. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…29 Second, elevation in total IgE is known to occur following BMT; however, this appears to be a transient phenomenon that occurs early after BMT without long-term persistence. 30,31 Other diagnoses could mimic asthma in this patient population, especially BO syndrome in those with GVHD. However, this is unlikely to have confounded the results of this study because all patients with asthma reported allergic triggers for their asthma symptoms and BO was specifically excluded in 1 of the 2 patients with chronic GVHD.…”
Section: Discussionmentioning
confidence: 91%
“…29 Second, elevation in total IgE is known to occur following BMT; however, this appears to be a transient phenomenon that occurs early after BMT without long-term persistence. 30,31 Other diagnoses could mimic asthma in this patient population, especially BO syndrome in those with GVHD. However, this is unlikely to have confounded the results of this study because all patients with asthma reported allergic triggers for their asthma symptoms and BO was specifically excluded in 1 of the 2 patients with chronic GVHD.…”
Section: Discussionmentioning
confidence: 91%
“…Mean serum IgD levels or the proportion of individuals with high levels of IgD were increased in a variety of disorders with immune activation and immunodeficiencies, usually associated with increases in other immunoglobulin isotypes. However, a significant number of individuals had low levels in these disorders which included HIV infection [8][9][10], chronic bronchopulmonary aspergillosis [11], Down's syndrome [12], acute hepatitis and salmonellosis [13], atopies [14], chronic obstructive pulmonary disease [15] and hyper-IgE syndrome [16,17], This was also the case in disorders not usually associated with other forms o f hypergammaglobuli nemia such as Hodgkin's disease [18], tuberculosis [19], in children following chemotherapy for malignancy [20], and after bone marrow transplantation [21]. Even in one disor der defined by high levels of IgD, the hyper-IgD syndrome, normal levels were occasionally observed [22], Significant ly decreased levels were observed in some immunoglobulin deficiency states-non-X-linked agammaglobulinemia [17] and IgA deficiency [17,23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IgE levels are often raised in recipients receiving marrow from non‐atopic donors [6]. The evidence that serum IgE levels rise with the onset of GvHD or infection is conflicting; some studies report an association, whilst others demonstrate no temporal correlation [7, 8]. The rise is not related to myeloablative chemotherapy as it has been observed in immunodeficient children transplanted without chemotherapy [9].…”
mentioning
confidence: 99%
“…Serum IgE rise is preceded by an increase in a soluble CD23 product, thought to be a fragment of the low‐affinity IgE receptor, and probably released during the immunoregulatory imbalance immediately post‐transplantation [10]. In the immediate post‐transplant period it is likely that donor‐derived IgE‐secreting mature B cells are released from the normal T cell regulation, allowing an uncontrolled release of IgE, until regulatory T cells have re‐populated [8]. However, GvHD is characterized by cellular degeneration and damage, mediated by activated macrophages and a Th1‐type response [11].…”
mentioning
confidence: 99%